Free zones in Algeria: Between the necessity of integration and opportunities for activation to enhance investment’. A review in light of current legislation and regulation’ - Nouha, Chirouf (The International tax journal, 2025)
The changes made by the Algerian state to its legal system are an important step towards establishing a market economy characterised by investment, competitiveness and multifaceted development, with the aim of achieving stability in the social and economic environment within its geographical scope. This includes creating opportunities for national and foreign investment in industry, trade and services. The issuance of Law No. 22-15 on 20 July 2022 was therefore necessary, as it defines the rules governing free zones and supports investment by granting investors privileges regarding management, taxation, and customs, in accordance with the legally established conditions and procedures assigned by Law No. 22-18 on investment, also dated 24 July 2022. Furthermore, Executive Decree No. 24-168, dated 28 May 2024, specifies the methods for granting management privileges for free zones. This requires an analysis of the legal controls adopted by the Algerian legislator to prepare and direct free zones in order to attract investment and provide guarantees.